Cardiac chloride channels: physiology, pharmacology and approaches for identifying novel modulators of activity. - Mulvaney, A; Spencer, C; Culliford, S; Borg, J; Davies, S; Kozlowski, R (2000)
Drugs that block cardiac cation channels have been marketed as the therapeutic answer to cardiac arrhythmia. However, such molecules have been only moderately successful at improving the survival of cardiac patients, and so new targets have been needed for future antiarrhythmic agents. This article outlines the properties and roles of Cl(-) channels, which are one of these new targets, and describes an approach for identifying novel CI(2) channel modulators.